Neurodegeneration and Sensorimotor Deficits in the Mouse Model of Traumatic Brain Injury - Saurav Bhowmick; Veera D‘Mello; Nizmi Ponery; P. M. Abdul Muneer (Brain Sciences)
Traumatic brain injury (TBI) can result in persistent sensorimotor and cognitive deficits, which occur through a cascade of deleterious pathophysiological events over time. In this study, we investigated the hypothesis that neurodegeneration caused by TBI leads to impairments in sensorimotor function. TBI induces the activation of the caspase-3 enzyme, which triggers cell apoptosis in an in vivo model of fluid percussion injury (FPI). We analyzed caspase-3 mediated apoptosis by terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) staining and poly (ADP-ribose) polymerase (PARP) and annexin V western blotting. We correlated the neurodegeneration with sensorimotor deficits by conducting the animal behavioral tests including grid walk, balance beam, the inverted screen test, and the climb test. Our study demonstrated that the excess cell death or neurodegeneration correlated with the neuronal dysfunction and sensorimotor impairments associated with TBI.